Synthesis of mixed salts of the [Mo2O2(μ-S)2(SCN)6-n(L)n](4+n)− anion (n = 0–2); structures of [Mo2O2(μ-S)2(SCN)5(CH3CN)]3−, [Mo2O2(μ-S)2(CN)5]3−, and [Mo2O2(μ-S)2(CN)2(O)]2−, and probing the ligand exchange of thiocyanate and cyanide. (15th November 2021) - Suman, Sigridur G.; Snæbjörnsson, Thorvaldur; Ragnarsdóttir, Oddný; Polukeev, Alexey V.; Wendt, Ola F.
Graphical abstract: Coordination of cyanide in aqueous solution is a desireable way to sequester cyanide. A very fast ligand exchange reaction of coordinated isothiocyanato ligands with cyanide resulted in pentakis cyano coordinated [Mo2 O2 (µ-S)2 ] 2+ core. Hydrolysis of the cyanide complex in water included dissociation of the cyanide and formation of the MoO moiety Successful sequestering may depend on prompt removal of the cyano complex from water. Abstract: Aqueous coordination of cyanide and verification of the composition of the resulting coordination compound is important to ensure confidence in its coordination. Isothiocyanato compounds 1 –7 were synthesized employing different synthetic routes and the complex, [Mo2 O2 (μ-S)2 (SCN)5 (CH3 CN)] 3−, 4, was structurally characterized. Ligand exchange reaction of 4 with cyanide forms 8, a cyano complex. Complex 8 was isolated as an organosoluble salt and fully characterized and confirmed as the major product formed in the aqueous ligand exchange reaction of 4 –7 with cyanide. The crystal structure of 8 revealed the unusual [Mo2 O2 (μ-S)2 (CN)5 ] 3− anion where the two molybdenum(V) centers are unsymmetrically coordinated. A second unsymmetric cyano complex [Mo2 O3 (μ-S)2 (CN)2 ] 2− 9, presumed hydrolysis product from an aqueous reaction, was isolated and structurally characterized revealing one square pyramidal Mo center and one tetrahedral Mo center in the binuclear core. Attempts to quantify the first order dissociative ligand substitution rate of thiocyanate in 4 to form 8 using the stopped-flow method gave an estimated minimum rate constant of 70 s −1 . This confirms that the exchange reaction is sufficiently fast to be useful in aqueous coordination of cyanide.